Investigation of airborne nanoparticles: the focus on Analytical Chemistry - Smichowski, Patricia Nora; Gomez, Dario Ruben (Royal Society of Chemistry, 2022)
Fil: Smichowski, Patricia Nora. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina